Melt spinning of polyethylene composite fibers containing disentangled ultra-high molecular weight polyethylene - Yan, Xiang; Zhang, Yu; Li, Wei; Wang, Jingdai; Yang, Yongrong (Wydawnictwo Politechniki Łódzkiej, 2022)
The commercial entangled ultra-high molecular weight polyethylene (UHMWPE) shows a high degree of entanglement in macromolecular chains, and our research group used the modified Ziegler-Natta catalyst to prepare UHMWPE with a low degree of entanglement to improve its melt processability. The application on plate-like material formed by injection or hot pressing has been explored, and at present we would like to expand the application field to fibers and textiles. The disentangled UHMWPE is added into the high-density polyethylene (HDPE) matrix by using twin screw extrusion for subsequent melt spinning process. The experimental results show that the addition of ultra-high molecular weight polyethylene improves the mechanical properties of fibers, and the effect varies with the addition amount. The addition amount of UHMWPE is optimized as 45 wt.%, which significantly improves the tensile strength of HDPE from 3.7 to 7.7 cN/dtex.
Keywords: melt spinning; ultra-high molecular weight polyethylene (UHMWPE); disentanglement; przędzenie ze stopu; polietylen o ultra wysokiej masie cząsteczkowej (UHMWPE); rozplątywanie